2021
DOI: 10.3390/jof7100787
|View full text |Cite
|
Sign up to set email alerts
|

The First Whole Genome Sequencing of Sanghuangporus sanghuang Provides Insights into Its Medicinal Application and Evolution

Abstract: Sanghuangporus is a medicinal macrofungal genus typified by S. sanghuang, the very species utilized in traditional Chinese medicines by Chinese ancient people. To facilitate the medicinal application of S. sanghuang, we, for the first time, perform its genome sequencing and analyses from a monokaryon strain. A 33.34 Mb genome sequence was assembled to 26 contigs, which lead to the prediction of 8278 protein-coding genes. From these genes, the potential biosynthesis pathway of sesquiterpenoids was, for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…S13). There were 126 coding genes (143 proteins) identified and divided into 14 cytochrome P450 families, with the CYP5144 family having the most P450s ( 52 ), followed by the CYP512 ( 31 ), CYP5141 ( 14 ), CYP5037 ( 11 ), and CYP5035 ( 10 ) families. The remaining nine families all have no more than 10 members, accounting for about 16% in total.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S13). There were 126 coding genes (143 proteins) identified and divided into 14 cytochrome P450 families, with the CYP5144 family having the most P450s ( 52 ), followed by the CYP512 ( 31 ), CYP5141 ( 14 ), CYP5037 ( 11 ), and CYP5035 ( 10 ) families. The remaining nine families all have no more than 10 members, accounting for about 16% in total.…”
Section: Resultsmentioning
confidence: 99%
“…The resolution of genomic information on wood-dwelling macrofungi will help to understand their life cycle, mating types, and nutritional models. To date, the genomes of several valuable medicinal (edible) fungi, including Ganoderma lucidum ( 25 , 26 ), Inonotus obliquus ( 27 ), Hericium erinaceus ( 28 ), Naematelia aurantialba ( 29 ), Antrodia camphorata ( 30 ), and Sanghuangporus sanghuang ( 31 ), have been deciphered, thereby further facilitating their medicinal utilization and industrial development. L. sulphureus is a wood-dwelling-type medical and edible fungus that has attracted much attention, although the genomes of its five subspecies ( 10 , 32 34 ) have been sequenced and used to analyze the lignocellulosic biomass degradation characteristics ( 10 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…After fermentation, the spore cells were collected by centrifugation at 8000× g for 5 min, and sterile water (three rinses) was used to remove the medium and metabolites attached to the spore cell surface. The sodium dodecyl sulfate (SDS) method was used to extract the genomic DNA, and agarose gel electrophoresis was performed to check its integrity [23].…”
Section: Extraction Of Genome Dnamentioning
confidence: 99%
“…The medicinally valuable sang'huang recorded in the ancient book of traditional Chinese medicine has previously been considered as Sanghuangporus baumii and Sanghuangporus vaninii; yet, Ying et al clarified its taxonomic status by comparative genomic analysis and named it sanghuangporus sangguang [22,23]. The golden needling mushroom in East Asia has been reported as Asian Flammulina velutipes or Flammulina velutipes var.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more studies have reported on the results of fungal genome sequencing. Genome-wide sequencing of fungi from Hymenochaetaceae has revealed their biological activity value ( Huo et al, 2020 ; Jiang et al, 2021 ). The genome sequencing results also provide a strong research basis for our understanding of fungal function and ingenuity.…”
Section: Introductionmentioning
confidence: 99%